Mutational Effects of Mobile Introns on the Mitochondrial Genomes of Metschnikowia Yeasts - Thompson, Scout R. L.; Lee, Dong Kyung; Lachance, Marc-André; Smith, David Roy (Frontiers in Genetics, 2021)
It has been argued that DNA repair by homologous recombination in the context of endonuclease-mediated cleavage can cause mutations. To better understand this phenomenon, we examined homologous recombination following endonuclease cleavage in a native genomic context: the movement of self-splicing introns in the mitochondrial genomes of Metschnikowia yeast. Self-splicing mitochondrial introns are mobile elements, which can copy and paste themselves at specific insertion sites in mitochondrial DNA using a homing endonuclease in conjunction with homologous recombination. Here, we explore the mutational effects of self-splicing introns by comparing sequence variation within the intron-rich cox1 and cob genes from 71 strains (belonging to 40 species) from the yeast genus Metschnikowia. We observed a higher density of single nucleotide polymorphisms around self-splicing-intron insertion sites. Given what is currently known about the movement of organelle introns, it is likely that their mutational effects result from the high binding affinity of endonucleases and their interference with repair machinery during homologous recombination (or, alternatively, via gene conversion occurring during the intron insertion process). These findings suggest that there are fitness costs to harbouring self-splicing, mobile introns and will help us better understand the risks associated with modern biotechnologies that use endonuclease-mediated homologous recombination, such as CRISPR-Cas9 gene editing.